Laporan survey kawasan desa di hulu DAS Malinau, kecamatan Malinau (19 Pebruari s/d 4 Maret 1999) - Laway, P.S.S.T.; Bil, Y. (WWF-Kayan Mentarang, CIFOR, PLASMA, 1999)
This report is the first of two survey reports. The survey was undertaken at Malinau Watershed area from 19 February -4 March 1999. Although this is not a full report, the information and its reviews are relevant for discussion and follow up. The objectives of the survey carried out by relevant institutions are to: (1) seek preliminary information on villages, their communities, history and adat forests along the Malinau watershed; (2) collect preliminary data on forest and natural forest management systems carried out by adat communities and their adat law; (3) have general picture of conflicts and potential conflicts in villages along the Malinau watershed and local institution readiness in solving the existing conflicts; (4) obtain preliminary information on communities' and local institutions' preparedness in mapping their adat forests; and (5) promote and encourage participatory mapping activities.